Peran Strategis Problem-Based Learning Dalam Mengoptimalkan Keterampilan Pemecahan Masalah Siswa Sekolah Dasar Pada Mata Pelajaran PPKN - Putri Sugiharto, Anggie; Amelia Amri, Mira; Putra, Adi (IJPSE Indonesian Journal of Primary Science Education, 2025)
This study aims to explore the effectiveness of the Problem-Based Learning (PBL) approach as an instructional strategy that fosters students’ problem-solving abilities in real-world contexts, particularly in the teaching of Civics Education (PPKn) at the elementary school level. A qualitative descriptive method was employed through a literature review of 42 national and international scholarly articles, which were then narrowed down to the 10 most relevant sources based on contextual relevance, publication quality, and thematic focus. The findings indicate that PBL consistently encourages students to think critically, address contextual problems, and engage actively in group discussion and collaboration. Moreover, this approach enhances students’ understanding of civic values, cultivates reflective thinking, and promotes social responsibility. The study highlights the importance of repositioning the teacher’s role—from a transmitter of knowledge to a facilitator who stimulates students’ active participation and independent thinking. These findings offer practical implications for developing a more participatory, contextual, and transformative learning strategy in Civics Education, particularly one aligned with the developmental characteristics of elementary students. Ultimately, the research contributes to the advancement of pedagogical models aimed at shaping young citizens who are solution-oriented and embody the values of Pancasila.